INTEGRATION OF CHARACTER EDUCATION IN SCHOOLS: THE CHARACTER SCHOOL EXPERIENCE - Made Ayu Anggreni; Andrianus Prihartanto; Rossa Ramadhona (International Journal of Teaching and Learning, 2024)
The use of character education in learning, however, is an absolute necessity, because it is considered capable of making students intelligent, but also ready to make students have character and habits so that they become real citizens. be significant both for them and society as a whole. Character education teaches habits of thinking and behavior that help individuals to live and work together as a family, community and nation and helps them to make responsible decisions. In other words, character education teaches students to think intelligently, activating the midbrain naturally. Character education is carried out in an integrated manner into all subjects. The integration in question includes loading values into the substance of all subjects and implementing learning activities that facilitate the practice of values in every activity inside and outside the classroom for all subjects. Character education is also integrated into the implementation of student development activities. Apart from that, character education is carried out through activities. The integration of character education in the learning process at school is carried out from the planning, implementation, to learning evaluation stages in all subjects.